The Frequency and Densıty of Weeds in Peanut (Arachis hypogaea L.) Fıelds of Adana Provınce, Türkiye - Harun Alptekin; Ramazan Gürbüz; Ramazan Taşkın (Research in Agricultural Sciences)
Peanut (Arachis hypogaea L.) is an important arable crop. However, weeds cause significant yield losses difficulties. This study was conducted to determine the occurrence frequency and density of weed species in peanut fields in Adana province. In the 2021 vegetation period, surveys were conducted in 50 peanut fields in Adana and its districts. As a result of the surveys, 38 weed species belonging to 17 different families were identified. The Poaceae family had the highest number of weed species with 12 species, followed by the Amaranthaceae family with 4 species. Other important families included Euphorbiaceae, Asteraceae, Cyperaceae, Convolvulaceae, Malvaceae, and Solanaceae, each represented by 2 species. The studies showed that most of the weeds in peanut fields were broadleaf and annual species. According to survey results, species such as Cyperus rotundus L. (78%), Sorghum halepense (L.) Pers (67%), Xanthium strumarium L. (52%), Convolvulus arvensis L. (49%), and Portulaca oleracea L. (46%) were among the most common weeds in the region with the highest occurrence frequencies. In terms of density, Setaria viridis (L.) P. Beauv. (1,050 plants/m²) had the highest density. Other dense species included C. rotundus (0.715 plants/m²), Echinochloa colona L. (0.630 plants/m²), Echinochloa crus-galli (L.) P. Beauv. (0.505 plants/m²), and S. halepense (0.425 plants/m²). These species are dominant in the weed flora of the region with high occurrence frequencies and density levels.